Conceição Lima e a poesia na pós-independência em São Tomé - Medeiros, Francisco Roberto Silveira de Pontes (2014)
This article deals with the contemporary literature of São Tomé e Príncipe, in which is addressed Conceição Lima's poetry, author whose debut in book writing occurred with the collection O útero da casa(2004), followed by a second book, A dolorosa raizdo micondó(2006). The analysis is made in about eight poems of the author to verify her belonging to the isle country and the content of unsubmissive poetry of her verses in the context of post-independence.